Functional feeding groups and spatial variation of aquatic insects in a hydrographic basin of Southern Brazil - Mario Arthur Favretto; Elton Orlandin; Emili Bortolon dos Santos; Osvaldo Onghero-Junior (Acta Biológica Catarinense, 2018)
In Brazil, river basins are geographic units used for environmental and water resources management. Few studies focus on the variation of biodiversity in these units. We present the results on the spatial variation of aquatic insects in streams of the catchment area of Peixe River, southern Brazil. The insect composition was analyzed for relative abundance of families, functional trophic group and environmental assessment indices. The insects had a heterogeneous distribution among the sample areas of the basin. The most abundant families were Hydropsychidae, Philopotamidae and Leptophlebiidae, a fact that shows a good oxygenation in the waters of these streams. The most abundant functional trophic groups were collector-collector (20%) and scraper (18.92%). The indices indicate that the bed of the streams is stable, with a high presence of fine particulate organic matter, being considered heterotrophic. However, the indices also indicated a low abundance of shredders, which may be related to unsatisfactory environmental conditions in the riparian forests. Spatial variation was found in aquatic insects and the indices indicated that the main human impacts on the streams may originate from deforestation and inadequate soil use. Data obtained also contribute to reinforce the importance of watersheds as geographic units for environmental conservation.